The letters of Hildegard of Bingen. - Hildegard, Saint, 1098-1179 (Oxford University Press, 1998)
The first translation into English of the complete correspondence of the remarkable twelfth-century Benedictine abbess Hildegard of Bingen (1098-1179), this study consists of nearly four hundred letters, in four projected volumes. Addressed to some of the most notable people of the day, as well as to some of humble status, the correspondence reveals the saint in ways her more famous works leave obscure: as determined reformer, as castigating seer, as theoretical musician, as patient adviser, as exorcist. Sometimes diffident and restrained, sometimes thunderously imperious, her letters are indi.